Asuhan Keperawatan Anak Pada Pasien Dengan Asma Bronkial Diruang Anak RSUD Prof. H. Muhammad Yamin, Sh Pariaman Tahun 2026 - Yushika Syelvira; Prima Yoselina; Reska Handayani; Yessy Aprihatin (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Bronchial asthma is a chronic respiratory disease characterized by airway inflammation, bronchospasm, and increased mucus production, which can lead to breathing difficulties. The purpose of this study was to improve the quality of nursing care in managing pediatric patients with bronchial asthma in a comprehensive manner. This study employed a case study method conducted from March 3 to March 7, 2026, in the pediatric ward of RSUD Prof. H. Muhammad Yamin, SH Pariaman. The nursing care approach included assessment, diagnosis, intervention, implementation, and evaluation, with data collected through interviews, observation, physical examination, and documentation.The subject of this study was a pediatric patient (An. A) diagnosed with bronchial asthma who was hospitalized for five days. The results identified three nursing problems: ineffective airway clearance, ineffective breathing pattern, and activity intolerance. After implementing interventions such as airway management, respiratory monitoring, and energy management, the patient’s condition improved, as indicated by reduced shortness of breath, a more regular breathing pattern, and increased activity tolerance. These findings suggest that the nursing care provided was effective in improving the patient’s condition.It is recommended that patients and their families maintain proper home care and ensure a clean and healthy environment by regularly cleaning dust, avoiding exposure to cigarette smoke and air pollution, refraining from keeping furry pets indoors, and maintaining proper home ventilation to support good air circulation and prevent respiratory illnesses among family members.